2003
DOI: 10.1016/s0008-6223(02)00270-1
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen plasma modification of pitch-based isotropic carbon fibres

Abstract: International audienceAn isotropic carbon fibre was surface-treated by microwave oxygen plasma at different conditions and characterised by scanning electron microscopy (SEM), scanning tunneling microscopy (STM), N2/CO2 adsorption, Raman spectrometry, X-ray photoelectron spectroscopy (XPS) and temperature-programmed desorption (TPD). It is shown that the structure of the fibre suffers only limited alterations upon plasma treatment in such a way that the local disorder on its surface, which was already large in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
91
0
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(101 citation statements)
references
References 80 publications
(47 reference statements)
6
91
0
4
Order By: Relevance
“…Surface modification imparts various functional groups, such as hydroxyl, carboxyl, amine and vynil, and their adsorption onto CNTs surface is responsible for the various physicochemical and catalytic properties of the modified material. These oxygen containing functional groups can be introduced by mechanical [26], chemical [27] and electrochemical techniques [28]. The amount and type of attached functional groups strongly depends on the type of surface modification applied.…”
Section: Introductionmentioning
confidence: 99%
“…Surface modification imparts various functional groups, such as hydroxyl, carboxyl, amine and vynil, and their adsorption onto CNTs surface is responsible for the various physicochemical and catalytic properties of the modified material. These oxygen containing functional groups can be introduced by mechanical [26], chemical [27] and electrochemical techniques [28]. The amount and type of attached functional groups strongly depends on the type of surface modification applied.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, Boudou et al [15] confirmed by SEM and STM analysis that the pitch-based carbon fibres treated in low pressure (1.0 mbar) oxygen MW plasma during 1-5 min keep their structure and diameter. At the same time, the carbon surface is cleaned from contaminations and the specific surface area (SSA) is increased due to improved roughness.…”
Section: Introductionmentioning
confidence: 89%
“…For example, oxygen or air plasma leads to the oxidation of carbon surface [15][16][17][18][19][20][21][22][23][24][25][26][27]. Nitrogen and ammonia plasmas introduce C/N functionality on carbon surface [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanical interlocking provided a strong interface bonding even though other effects were relatively weak [15]. In addition, the enhancement of the surface roughness reduced the contact angle between fibers and PI and hence increased the wettability [16].…”
Section: Morphology Analysismentioning
confidence: 99%